Molecular Identification of Anion Exchange Protein 3 in Pacific White Shrimp (Litopenaeus vannamei): mRNA Profiles for Tissues, Ontogeny, Molting, and Ovarian Development and Its Potential Role in Stress-Induced Gill Damage - Zhang, Xin; Yang, Hao; Li, Hongmei; Chen, Ting; Ruan, Yao; Ren, Chunhua; Luo, Peng; Wang, Yanhong; Liu, Bing; Li, Huo; Zhong, Ping; Zhang, Jiquan; et al. (Frontiers in Physiology, 2021)
Bicarbonate (HCO3-) transport mechanisms play an essential role in the acid-base homeostasis of aquatic animals, and anion exchange protein 3 (AE3) is a membrane transport protein that exchanges Cl-/HCO3- across the cell membrane to regulate the intracellular pH. In this study, the full-length cDNA of AE3 (Lv-AE3) was obtained from the Pacific white shrimp (Litopenaeus vannamei). The Lv-AE3 cDNA is 4943 bp in length, contains an open reading frame (ORF) of 2850 bp, coding for a protein of 949 amino acids with 12 transmembrane domains. Lv-AE3 shows high sequence homology with other AE3 at the protein level. Lv-AE3 mRNA was ubiquitously detected in all tissues selected, with the highest expression level in the gill, followed by the ovary, eyestalk and brain. By in situ hybridization, Lv-AE3-positive cells were shown predominant localization in the secondary gill filaments. The expression levels of Lv-AE3 were further investigated during the essential life processes of shrimp, including ontogeny, molting and ovarian development. In this case, the spatiotemporal expression profiles of Lv-AE3 in L. vannamei were highly correlated with the activities of water and ion absorption; for example, increased mRNA levels were present after hatching, during embryonic development, after ecdysis during the molt cycle, and in the stage IV ovary during gonadal development. After low/high pH and low/high salinity challenges, the transcript levels of Lv-AE3 were reduced in the gill, while the cell apoptosis rate increased. In addition, knockdown of Lv-AE3 mRNA expression induced cell apoptosis in the gill, indicating a potential link between Lv-AE3 and gill damage. Altogether, this study may supply new insights into the molecular mechanism of pH and osmotic regulation of L. vannamei, and it may benefit the protection of cultured shrimp from fluctuated aquatic environments.